LFC of Multimachine Power System Incorporated With Plug-in Electric Vehicle Fleets - Biswas, Jyotirmoy; Bera, Parthasarathi; Chakrabarty, Krishnendu (Annual IEEE India Conference, 2024)
Due to the stochastic nature of various renewable sources, different energy storages are being used for frequency stability of modern day power system. Electric Vehicles (EVs) being suitable and the most available form of distributed energy storages, those are being used for different ancillary services with the grid. Bidirectional power transfer capability of the power converters of the EV battery chargers has made it capable of being considered as necessary power reserve during frequency fluctuations due to mismatch between power generation and demand. As the vehicle-to-grid technology depends on EV aggregators to locate the position and State of charge (SOC) of the EVs through the charging stations, instead of scattered EVs, in this paper, the aggregate model of the EV fleets are incorporated in each of the three areas of 39-Bus New England Power System, segregated using a deterministic method, to investigate effect of those in load frequency control (LFC) study of the system. Furthermore, a latest fuzzy gain scheduled PID control (FGS-PIDC) technique along with its performance comparison with Conventional PID controller (PIDC) as load frequency controller is shown in this paper. For optimization of the parameters of FGS-PIDC and PIDC Multi-objective Grey Wolf Optimization Algorithm (MOGWOA) is used.